TOKOH PEREMPUAN DAN NILAI-NILAI PENDIDIKAN KARAKTER DALAM NASKAHLAKON SUSI DUYUNG LUDRUK BUDHI WIJAYA (KAJIAN FEMINISME) - Ninik Nur Khasanah (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2018)
This study aims to describe: (1) The struggle of female characters in realizing feminism in the script of the play "Susi Duyung" Ludruk Budhi Wijaya (2) Gender in the script of the play "Susi Duyung" Ludruk Budhi Wijaya (3) Character education contained in the play "Susi Duyung ”Ludruk Budhi Wijaya. The method used in this study is a qualitative descriptive method with a Feminism approach. The source of research data is the text of the play Susi Duyung Ludruk Budhi wijaya. The main data in the research is in the form of a manuscript. Data collection techniques use note-taking techniques. Researchers play a direct role as the main instrument of research. Data validation was obtained through triangulation of data sources and theory. Data analysis used by the research is a flow analysis model by collecting data, reducing data, presenting data, and verifying data.The results obtained from the study showed that: (1) the struggle of women in realizing feminism is liberal feminism (2) gender found in the script of Susi Duyung's play namely marginalization of women, violence, and workload (3) The value of character education that emerged in this study is the value of responsibility, the value of hard work, independent values, honest values, values ??of discipline, value of curiosity, creative value, democratic values, religious values ??and values ??of respect for achievement. Keywords: Feminism, Gender and Character Education Value